1997
DOI: 10.1038/sj.bjp.0701048
|View full text |Cite
|
Sign up to set email alerts
|

Functional role of M2 and M3 muscarinic receptors in the urinary bladder of rats in vitro and in vivo

Abstract: 1 Urinary bladder smooth muscle is enriched with muscarinic receptors, the majority of which are of the M 2 subtype whereas the remaining minority belong to the M 3 subtype. The objective of the present study was to assess the functional role of M 2 and M 3 receptors in the urinary bladder of rat in vitro and in vivo by use of key discriminatory antagonists. 2 In the isolated bladder of rat, (+)-cis-dioxolane produced concentration-dependent contractions (pEC 50 =6.3) which were unaected by tetrodotoxin (0.1 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

24
229
5
4

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 292 publications
(262 citation statements)
references
References 42 publications
24
229
5
4
Order By: Relevance
“…These data demonstrate that contraction of human bladder in response to carbachol is mediated predominantly if not exclusively by the M 3 muscarinic receptor. This situation mimics closely the previously reported ®ndings in rats (Choppin et al, 1998;Hegde et al, 1997;Longhurst et al, 1995;Longhurst & Levendusky, 2000;Tong et al, 1997), mice (Choppin & Eglen, 2001b), pigs (Yamanishi et al, 2000) and dogs (Choppin & Eglen, 2001a). These data suggest that a drug for the e ective treatment of overactive bladder should have high a nity for M 3 receptors.…”
supporting
confidence: 90%
See 3 more Smart Citations
“…These data demonstrate that contraction of human bladder in response to carbachol is mediated predominantly if not exclusively by the M 3 muscarinic receptor. This situation mimics closely the previously reported ®ndings in rats (Choppin et al, 1998;Hegde et al, 1997;Longhurst et al, 1995;Longhurst & Levendusky, 2000;Tong et al, 1997), mice (Choppin & Eglen, 2001b), pigs (Yamanishi et al, 2000) and dogs (Choppin & Eglen, 2001a). These data suggest that a drug for the e ective treatment of overactive bladder should have high a nity for M 3 receptors.…”
supporting
confidence: 90%
“…Nevertheless analysis of the shifts of the carbachol concentration response curve yielded slopes close to unity for all four antagonists. The rank order of the antagonist potencies (atropine5darifenacin4pirenzepine4methoctramine) as well as the absolute potencies were in good agreement with those at cloned M 3 receptors and those determined functionally for antagonist of contraction in rat, mouse and dog bladder (Choppin & Eglen, 2001a, b;Hegde et al, 1997). These data demonstrate that contraction of human bladder in response to carbachol is mediated predominantly if not exclusively by the M 3 muscarinic receptor.…”
supporting
confidence: 71%
See 2 more Smart Citations
“…In this preparation, all muscarinic subtypes are expressed and their activation evokes micturition. Consensus evidence indicates that the pharmacological effects mediated by the different subtypes are hard to distinguish (Hegde et al, 1997) and that, in preparations from normal bladders with an intact urothelium, studies indicate that carbachol contraction is mediated by a homogenous muscarinic type 3 population (Hegde et al, 1997). In this tissue exposed to carbachol, mimicking increased cholinergic tone, we demonstrated that the addition of T1AM reduced contraction calculating an IC50M perfectly overlapping with pKi values measured from binding experiments.…”
Section: Discussionmentioning
confidence: 57%